Efficiency and Distributional Effects of the Two-Tracked Labor Market Institutions in Albania - Elvisa Drishti; Ermira Hoxha Kalaj; Bresena Dema Kopliku (Global Labor Organization (GLO), 2021)
This study examines the efficiency and distributional effects of selected labor market institutions in Albania, a rather underresearched country. An initial overview of the postcommunist developments articulates why Albania has the poorest labor market performance among other South East European countries. Using a set of mixed qualitative and descriptive quantitative methods we find evidence of inefficient segmental effects and a predatory structure of labor market institutions which noticeably diverge from the efficient institutions' point of reference. The institutional/welfare regime at the cross-national level points out at a relationship between the labor market institutional framework and labor market performance, as measured by unemployment. At the country level, a disproportional relationship between the "de jure" labor market regulation and unemployment is identified, which is also moderated by the interaction between labor market and economic institutions.
Keywords: 330; Albania; Labor market regulation; Welfare regime; Unemployment; Labor market institutions